PTU-059 "i can cope right now, because i know where i have come from"; a qualitative exploration of the lived experience of young adults with inflammatory bowel disease. (22nd June 2015) - Brooks, AJ; Rowse, G; Ryder, A; Narula, P; Corfe, BM; Norman, P; Lobo, AJ
Abstract : Introduction: Young people (YP) living with inflammatory bowel disease (IBD) are at risk of increased psychological morbidity, with increased rates of anxiety and depression at a life stage characterised by change, exploration, risk-taking and identity development whilst learning to manage and adjust to living with IBD as an adult. This is in the context of a globally rising incidence in paediatric Crohn's disease (CD) with a peak onset in adolescence. However, despite this there remains little research exploring YPs perceptions and experiences of living with IBD. The aim of this first qualitative study was to explore the lived experiences of YP with IBD. Method: YP aged 19–21 years with a diagnosis of ulcerative colitis (UC) or CD at a single large teaching centre were recruited for a qualitative face-to-face interview with a single investigator. Interviews were conducted following a semi-structured interview schedule regarding; receiving a diagnosis, impact on relationships, ways of coping, identity and the future. Interviews were audio-recorded, transcribed and subject to in-depth interpretative phenomenological analysis (IPA) used in clinical and health psychology. Results: Seven patients were interviewed (4 CD, 3 UC), median age 20 years (range 19–21) with 43% (3/7) male. Through IPA the YPs accounts clustered around 4 super-ordinate themes with contradiction as an overarching theme, with several sub-themes illustrating experiences of living with IBD; 1) coping with uncertainty and unpredictability ; included misdiagnosis, mislabelling, "everyone is different" and "takes years to make sense of it" 2) living with invisibility and visibility ; included "losing myself", embarrassment, disgust and use of humour. 3) Lack of compassion for self ; included a contradiction of control and lack of control, being limited by yet not held back, stoic and hiding emotions. 4) Resilience ; included positive impact on relationships and a positive outlook. Conclusion: The findings of this first qualitative study to investigate the lived experience of YP with IBD highlights key areas for enabling other YP to make sense of a diagnosis of IBD. Furthermore, improving health care professionals (HCPs) understanding of the experiences of YP may improve relationships and encourage positive changes in psychological health, social interactions and capacity for self-management. This in turn may inform development of high quality, young-person friendly healthcare services, described as the 'Cinderella' of the NHS. Disclosure of interest: None Declared.